Maintenance of Membrane Integrity and Permeability Depends on a Patched-Related Protein in Caenorhabditis elegans. Issue 4 (5th February 2016) - Choi, Myung-Kyu; Son, Sangwon; Hong, Mingi; Choi, Min Sung; Kwon, Jae Young; Lee, Junho
Abstract: Membrane integrity is critical for cell survival, defects of which cause pathological symptoms such as metabolic diseases. In this study, we used ethanol sensitivity of the nematode Caenorhabditis elegans to identify genetic factors involved in membrane integrity. In C. elegans, acute exposure to a high concentration (7% v/v) of ethanol changes membrane permeability, as measured by propidium iodide staining, and causes paralysis. We used the timing of complete paralysis as an indicator for alteration of membrane integrity in our genetic screen, and identified ptr-6 as a gene that confers ethanol resistance when mutated. PTR-6 is a patched-related protein and contains a sterol sensing domain. Inhibition of two PTR-encoding genes, ptr-15 and ptr-23, and mboa-1, encoding an Acyl Co-A: cholesterol acyltransferase homolog, restored ethanol sensitivity of the ptr-6 mutant, suggesting that these ptr genes and mboa-1 are involved in the maintenance of membrane integrity and permeability. Our results suggest that C. elegans can be used as a model system to identify factors involved in metabolic diseases and to screen for therapeutic drugs.